Xiphidorus parthenus n. sp. (NEMATA: LONGIDORIEDADE) FROM BRAZIL - Monteiro, Ailton Rocha; Lordello, Luiz Gonzaga E.; Nakasono, Kazutoshi (REVISTA DE AGRICULTURA, 2015)
Xiphidorus parthenus n. sp. (NEMATA: LONGIDORIEDADE) FROM BRAZIL